ENHANCING PERFORMANCE AND COMPETITIVENESS IN HOSPITALITY ORGANIZATIONS - MATARARABA, PENI (ITB Journal Publisher, LPPM ITB, 2006)
This paper investigates the key resources and related key strategies that contribute the most to the enhancement of performance and competitiveness in multinational hotels. Using the interrelated resource and competence based theories of the firm, the case study approach including face-to-face interviews with key personnel in five multinational hotels was adopted. The findings of this research indicate that the key resources most capable of enhancing performance and competitiveness in hospitality organizations are human, organizational, technological, and reputational. Optimal related key strategies exemplified by the multinational hotels include paradigm shifts in employee and customer regard, creation of time as a resource through outsourcing or centralization and, multi-linkages within distribution and promotional networks.